Water depth affects submersed macrophyte more than herbivorous snail in mesotrophic lakes - Ren, Wenjing; Yao, Yiqian; Gao, Xiaoyu; Wang, Hao; Wen, Zihao; Ni, Leyi; Zhang, Xiaolin; Cao, Te; Chou, Qingchuan (Frontiers in Plant Science, 2024)
Introduction Water depth (WD) and snail abundance (SA) are two key factors affecting the growth of submersed aquatic plants in freshwater lake ecosystems. Changes in WD and SA drive changes in nutrients and other primary producers that may have direct or indirect effects on submersed plant growth, but which factor dominates the impact of both on aquatic plants has not been fully studied. Methods To investigate the dominant factors that influence aquatic plant growth in plateau lakes, a one-year field study was conducted to study the growth of three dominant submersed macrophyte (i.e., Vallisneria natans, Potamogeton maackianus, and Potamogeton lucens) in Erhai Lake. Results The results show that, the biomass of the three dominant plants, P.maackianus, is the highest, followed by P.lucens, and V.natans is the lowest. Meanwhile, periphyton and snails attached to P.maackianus are also the highest. Furthermore, WD had a positive effect on the biomass of two submersed macrophyte species of canopy-type P.maackianus and P.lucens, while it had a negative effect on rosette-type V.natans. Snail directly inhibited periphyton attached on V.natans and thereby increasing the biomass of aquatic plants, but the effect of snails on the biomass of the other two aquatic plants is not through inhibition of periphyton attached to their plants. Discussion The dominant factors affecting the biomass of submersed macrophyte in Erhai Lake were determined, as well as the direct and indirect mechanisms of WD and snails on the biomass of dominant submersed macrophyte. Understanding the mechanisms that dominate aquatic plant change will have implications for lake management and restoration.